Linguistic Features of Part-Whole Relations - Nersesyan, Gohar (Bulletin of Yerevan University B: Philology, 2023)
The given article examines the linguistic manifestations of the philosophical categories of part and whole, which are considered to be among the fundamental concepts of human life perception. The latter are characterized by their complex nature and conditioned not only with the problems of the relation between linguistic systems and their elements, but also with the matters of organization in the corresponding systems and regulation. The author touches upon the processes of integration and separation that are in the bases of understanding the laws of linguistic shifts, being the result of paradigmatic and syntagmatic parallelizations of elements as well as the close connection of part-whole relations and the concept of language level through which only the peculiarities of part-whole structures with all the complexity of their forms can be revealed.
Keywords: ordering; cognitive linguistics; holism; merism; part and element of the whole; identical features; distinctive features; paradigmatic and syntagmatic connections; language level